Effect of site of insemination on bovine fertility - Mehmet B. Ataman; İbrahim Taşal; Melih Aksoy; Fikret Karaca; Abdullah Kaya; Tevfik Tekeli (Eurasian Journal of Veterinary Sciences)
Effect ol site ol semen deposition on pregnancy rates ol artificially inseminated cattle were investigated. A total of 100 animals. 82 cows and 18 heifers, were divided into four groups and inseminated by depositing semen into corpus or cervix of the uterus or ipsi-or contralateral horn to the Graffian follicle. Pregnancy rales were 88, 72. 84 and 72 %, respectively. It was concluded that deposition of the semen into corpus uteri or ipsilateral horn to the ovulatory follicle increase pregnancy rates with Al and cervix uteri does not appear to be advantageous target for cattle.